2021
DOI: 10.7759/cureus.16822
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Robot-Guided Dual Cortical Bone Trajectory for Adjacent Segment Disease

Abstract: Here we present a novel application of cortical bone trajectory (CBT) fixation utilizing robotic guidance in a previously instrumented spine with a traditional pedicle screw (PS), obviating the need for a larger posterior incision, reducing the risk of infection, muscular dissection, and likely decreasing hospital length of stay. A 60-year-old woman with prior left L3-L4 extreme lateral interbody fusion and unilateral percutaneous PS placed at L3 to L5 presented with progressive bilateral lower-extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Melikian et al [ 87 ] published a case report on unilateral cortical trajectory screw instrumentation, allowing for posterior instrumentation without having to remove the existing PSs in the setting of ASD. Rho et al [ 88 ] first applied robotic placement of a CBT screw in the same pedicle as a prior traditional PS for ASD.…”
Section: Advantages Of Midlf In Spinal Revision Surgerymentioning
confidence: 99%
“…Melikian et al [ 87 ] published a case report on unilateral cortical trajectory screw instrumentation, allowing for posterior instrumentation without having to remove the existing PSs in the setting of ASD. Rho et al [ 88 ] first applied robotic placement of a CBT screw in the same pedicle as a prior traditional PS for ASD.…”
Section: Advantages Of Midlf In Spinal Revision Surgerymentioning
confidence: 99%
“…CBT screws are particularly suitable for use in revision surgery because CBT screws have special screw structure (small diameter and length, with tight threads) and can be inserted from the inner and inferior aspects to the outer and superior aspects through the pedicle, which allows close screw contact with cortical bone of the pedicle, and results in low rate of FJV [ 16 , 35 ]. Rho et al [ 36 ] reported the use of RA CBT screw placement using Mazor X robot in the treatment of a patient with adjacent segment degeneration after thoracolumbar surgery, they inserted CBT screw again in the same pedicle without removal of the original pedicle screw, the results showed that bilateral screw placement was completed successfully, without the occurrence of bony destruction, RA CBT screw placement was more minimally invasive and had shorter hospital stay when compared to traditional revision surgery. Zhang et al [ 28 ] conducted a retrospective study on 81 patients who underwent lumbar spine revision surgery via a posterior approach, 39 patients received pedicle screw placement using Mazor Renaissance, the remaining 42 patients received conventional FH pedicle screw placement, they found that the number of screws inserted was 267 in the Mazor Renaissance group and 288 in the conventional FH group, lumbar pedicular screw placement accuracy was 93% in the Mazor Renaissance group, and 87.1% in the conventional FH group.…”
Section: Clinical Application Scenarios For Spine Surgical Robotsmentioning
confidence: 99%
“…As robotic spinal surgery has become widely used, the advantages of a relatively short learning curve, high accuracy of robot-assisted screw placement, and short radiation exposure time have been highlighted. [8][9][10][11][12] In view of this, this study presented an analysis of the clinical data of 7 cases treated by the CBT screw fixation technique as a salvage strategy with the help of the Mazor Renaissance robot system to evaluate the therapeutic effect of this technique for failed lumbar spine surgery.…”
Section: Introductionmentioning
confidence: 99%